2020
DOI: 10.18231/2581-4729.2018.0062
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of periorbital dermatoses in a tertiary care hospital in South India

Abstract: Introduction: Periorbital dermatoses are the dermatological manifestations of the area around the eye excluding eyelid. It greatly affects quality of life. As there is lack of adequate data about frequency and distribution of periorbital dermatoses, there is need for studies to be conducted to study clinical patterns of periorbital dermatoses. Aesthetic facial concerns have been the main reason for dermatological consults in the last few years, one among which is the periorbital dermatoses. Methodology: It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
2
0
1
Order By: Relevance
“…The present study showed the predominant involvement of <10y age group; 25.9% of patients, in contrast to other studies [8][9][10][11][12][13]96-101 which reported the prevalence of an older age group. This variation may be related to the sample size and the differences in the demographic characteristics between India and Iraq, where these studies are conducted.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present study showed the predominant involvement of <10y age group; 25.9% of patients, in contrast to other studies [8][9][10][11][12][13]96-101 which reported the prevalence of an older age group. This variation may be related to the sample size and the differences in the demographic characteristics between India and Iraq, where these studies are conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the female patients 57.9% preponderates the males' 42.1% with a female to male ratio of 1.3:1. These facts were closely comparable to other reported studies [8][9][10][11][12][13][14]96-101. The reasons for sex related disparities remain unknown, and maybe multifactorial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation